Relationship between Smoking Activity and Chronic Obstructive Pulmonary Disease in the Zainoel Abidin General Hospital, Banda Aceh, Indonesia - Salawati, Liza; Husnah, Husnah; Nawawi, Yusuf; Muchlisin, Zainal A. (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Exposure to cigarette smoke is one risk factor that can lead to the development of chronic obstructive pulmonary disease (COPD). AIM: The aim of this study was to examine the relationship between smoking and the stage of COPD. METHODS: This study used a cross-sectional survey design. A total of 60 COPD patients were involved in the study between September and November 2015 at the pulmonary ward of Zainoel Abidin General Hospital (ZAGH), Banda Aceh, Indonesia. The data were analyzed with the non-parametric bivariate test. RESULTS: The results showed that 55% of patients with COPD were aged between 40 and 60 years; 63.33% of them were heavy smokers. About 50% of moderate smokers suffered from Stage III COPD, while 34.21% of heavy smokers suffered from Stage III and Stage VI (severe) COPD, respectively, with p = 0.007. CONCLUSIONS: There is a strong relationship between smoking and COPD stage among patients at ZAGH.